2005
DOI: 10.1086/497687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Type I Migration on Terrestrial Planet Formation

Abstract: Planetary embryos embedded in a gas disc suffer a decay in semimajor axis -- type I migration -- due to the asymmetric torques produced by the interior and exterior wakes raised by the body (Goldreich & Tremaine 1980; Ward 1986). This presents a challenge for standard oligarchic approaches to forming the terrestrial planets (Kokubo & Ida 1998) as the timescale to grow the progenitor objects near 1 AU is longer than that for them to decay into the Sun. In this paper we investigate the middle and late stages of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 40 publications
1
91
0
1
Order By: Relevance
“…It has been demonstrated by Kokubo & Genda (2010) that this a priori assumption of simple accretion does not significantly affect the results. The SyMBA code has already been used extensively in terrestrial planet formation simulations (Agnor et al 1999;Levison & Agnor 2003;O'Brien et al 2006;McNeil et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated by Kokubo & Genda (2010) that this a priori assumption of simple accretion does not significantly affect the results. The SyMBA code has already been used extensively in terrestrial planet formation simulations (Agnor et al 1999;Levison & Agnor 2003;O'Brien et al 2006;McNeil et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…R04 suggests that the presence of other embryos might prevent gap opening. However, direct dynamical simulations of problems with similar dynamics have shown that this is not the case (McNeil et al 2005;. In particular, gaps are opened in situations where the embryos are well separated, while the particles become trapped in the L 4 and L 5 Lagrange points if the embryos are closely packed.…”
Section: A Not-so Brief Review Of Core Accretion Modelsmentioning
confidence: 99%
“…Although ambitious, Chambers (2008) used semianalytic methods to follow the evolution of the planetesimals, and thus did not fully account for processes such as gap opening, which has been shown to negatively effect accretion rates in the sheardominated regime (McNeil et al 2005;. He also did not include the effects of planetesimal-driven planet migration (Fernandez & Ip 1984;Hahn & Malhotra 1999;Gomes et al 2004;Kirsh et al 2009).…”
Section: A Not-so Brief Review Of Core Accretion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…McNeil et al 2005). Type I decay is important for objects whose migration time scale t 1 is comparable to or shorter than the nebular lifetime t neb .…”
Section: (D ) Open Issuesmentioning
confidence: 99%